Microleakage in lithium disilicate veneers cemented with resin cement and thermally modified resin - Becerra Infantas, Gustavo Adolfo (2025)
Objective: To determine in vitro microleakage in lithium disilicate veneers cemented with resin cement and thermally modified resin. Materials and methods: An in vitro study was conducted using 20 maxillary premolars, on which lithium disilicate veneers were cemented. The specimens were divided into two groups of ten samples each. Each tooth was prepared on the vestibular surface for subsequent veneer fabrication. In Group 1, veneers were cemented with resin cement (Nexus-3), whereas in Group 2, thermally modified resin (Herculite Précis™) was used. Subsequently, the teeth underwent a thermocycling process and were immersed in a 2% methylene blue solution for five days, after which sagittal sections were performed for observation under an optical microscope. Results: A higher percentage of microleakage was observed in the group cemented with resin cement (47.5%; n = 19) compared to the group treated with thermally modified resin (32.5%; n = 13), with a p-value of = 0.018. Additionally, greater microleakage was detected at the cervical and mid-levels in the resin cement group compared to the thermally modified resin group, with a p-value of = 0.046. Conclusion: Microleakage was observed in both groups. When comparing the two luting agents, resin cement showed significantly greater microleakage than thermally modified resin.